Examining the role of conflict management strategies on employee retention: a conceptual approach - Yusuf, Ismaila; Abolade, Ayobami Paul (Management and Entrepreneurship: Trends of Development, 2025)
In today’s highly competitive business environment, employee retention has become a strategic imperative, particularly as organizations struggle with high turnover driven in part by ineffective conflict management systems. This study examines the influence of conflict management styles on employee retention, drawing on the Thomas-Kilmann Conflict Mode Instrument and Social Exchange Theory to explain how assertiveness, collaboration, and reciprocal workplace relationships shape employee commitment and organizational stability. Employing a meta-analytic approach, this study synthesizes findings from peer-reviewed research published between 2010 and 2023, focusing on the private sector. It integrates insights from both qualitative and quantitative studies to assess the relationship between specific conflict management styles integrating, compromising, dominating, avoiding, and accommodating and employee retention. Subgroup analyses and sensitivity tests were conducted to assess the consistency of results across different industries and organizational settings. The results indicate that integrating and accommodating conflict styles are consistently linked to higher employee retention and job satisfaction, with effect sizes ranging from r = 0.38 to β = 0.52. In contrast, avoidance and dominating styles correlate weakly or negatively with retention due to their failure to resolve core conflicts effectively. These findings emphasize the critical role of collaborative and empathetic conflict resolution in fostering long-term workforce stability. The study concludes that effective conflict management is essential for sustaining employee loyalty and organizational resilience. The study recommends that managers should proactively identify potential conflict areas and adopt context-appropriate strategies. Future research should employ mixed methods to fill methodological gaps and support evidence-based human resource practices. JEL Classification: О1, О2, О3, І31